STRATEGI PROMOSI MELALUI MEDIA PERIKLANAN DESA WISATA KUBU GADANG KOTA PADANG PANJANG - Nindy Eka Putri; Silfeni Silfeni; Feri Ferdian (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
The purpose of this research is to analyze the promotion strategy through advertising media at Desa Wisata Kubu Gadang Kota Padang Panjang view from 3 indicator: print media, electronic media, outdoor media. The research is a descriptive qualitative with survey method. Determination of informant using purposive sampling and snowball sampling. The purposive sampling technique involving 2 informant from tourism govermant and 2 informant from desa wisata Kubu Gadang Kota Padang Panjang manager then snowball sampling technique involving 3 informant from desa wisata Kubu Gadang Kota Padang Panjang visitor. Technique of collecting data is done by interview, observation, and documentation. The results of this study indicate that: 1) the strength of promotion advertising are: news paper easy to get, the picture quality on brochure have a good and interesting, radio can be heard anywhere, television give information through sound and picture, desa wisata Kubu Gadang also have a website and a big billboard with a perfect lighting. 2) the weakness of promotion advertising are: there was no promotion through a brochure, there was no update on the Kubu Gadang’s website, the billboard was vulnerable of damage. 3) the opportunities of promotion advertising are: there are many people who still interest to read the newspaper and brochure, there are many people who interest of internet using, many people can see the outdoor media as if billboard and baliho. 4) the threats of promotion advertising are: there are competitor through print media, television and outdoor media. The conclusion of The promotion strategy through advertising media at Desa Wisata Kubu Gadang Kota Padang Panjang is 1) making use of print media for promotion, 2) to increase the promotion thourgh radio, television and website/internet, 3) making advertising through outdoor media as if billboard and baliho.